Kebijakan Komunikasi dalam Penanganan Covid-19 di Provinsi Kepulauan Riau - Noni Kusnita; Irwan Syari Tanjung; Yogi Sumarsono Wibowo (Departement of Mathematics Education, 2022)
The policy for handling Covid-19 in the Riau Islands Province requires communication to provide information, educate and persuade to comply with health protocols and obey the regulations that have been set by the regional government of the Riau Islands province. Regulations which include the Enforcement of Restrictions on Community Activities or abbreviated as PPKM and Guidelines for the implementation of people's travel using sea transportation modes and ferry boats, and being willing to be vaccinated when a vaccination program is held by the government. The problem is how are the Guidelines for Implementing Community Transportation for the Mode of Sea Transportation or Ferry Boats during the Covid-19 pandemic in the regional government of the Riau Islands Province, how are the descriptions of communication messages about PPKM and the Instructions for Implementing Public Transportation for the Mode of Sea Transportation or Ferry Ships during the Covid-19 pandemic? 19 in the Regional Government of the Riau Archipelago Province. The policies carried out by the Government have principles including: openness in conveying data and information about Covid-19, Conducting interactive communication through radio channels to the public. Policies for handling Covid-19 are communicated through local mass media channels. The combination of communication media includes online media (new media) and social media. Policy messages regarding health protocols were also conveyed by placing pamphlets at a number of locations, banners and brochures in public service offices and government offices